2020
DOI: 10.1186/s41936-020-00155-1
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 fatty acids as feed supplement modulates blood formation and body weight in Rattus norvegicus model

Abstract: Background Omega-3 fatty acids’ inclusion as feed supplement in the diets of both human and animals has been found to play a significant role in body metabolism. The aim of this present study was to evaluate the effects of graded doses of omega-3 fatty acids on haematology and body weight of adult male and female Rattus norvegicus (Wistar albino rats) as a model animal. Methods A total of seventy-two adult male and female albino rats were randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…Although they showed varying values, statistically the WBC components (lymphocytes, monocytes, granulocytes, %lymphocytes, %monocytes, and %granulocytes) did not show a significant difference. This is in accordance with the research of Alia et al ( 2019) and Nnamonu et al (2020) which states that there is no significant difference to the WBC component. The increase in lymphocytes can be related to the release of the hormone epinephrine while the increase in monocytes is associated with phagocytic activity, inflammation, corticosteroids, secondary hemolysis and neoplasia ( Jackson, 2007).…”
Section: White Blood Cells Componentssupporting
confidence: 93%
See 3 more Smart Citations
“…Although they showed varying values, statistically the WBC components (lymphocytes, monocytes, granulocytes, %lymphocytes, %monocytes, and %granulocytes) did not show a significant difference. This is in accordance with the research of Alia et al ( 2019) and Nnamonu et al (2020) which states that there is no significant difference to the WBC component. The increase in lymphocytes can be related to the release of the hormone epinephrine while the increase in monocytes is associated with phagocytic activity, inflammation, corticosteroids, secondary hemolysis and neoplasia ( Jackson, 2007).…”
Section: White Blood Cells Componentssupporting
confidence: 93%
“…Although the values obtained varied, statistically the components of MCV, MCH, and MCHC did not have a significant difference, which was in accordance with the research of Alia et al ( 2019) and Nnamonu et al (2020). This statement is supported by the research of Babalola et al (2016) which stated that the provision of vegetable oil compared to fish oil did not show significant differences in MCV, MCH and MCHC.…”
Section: Comparison Of Blood Haematological Profilesupporting
confidence: 86%
See 2 more Smart Citations
“…The ndings of previous studies on hematological alteration effects of polyunsaturated omega-3 fatty acids as feed supplement have been controversial. Some of these studies have indicated positive effects of oral omega-3 supplements on hematological markers [2][3][4], while others did not nd these effects [5][6][7].…”
Section: Introductionmentioning
confidence: 99%